2019
DOI: 10.1002/aqc.3075
|View full text |Cite
|
Sign up to set email alerts
|

Benthic habitat modelling and mapping as a conservation tool for marine protected areas: A seamount in the western Mediterranean

Abstract: 1. An ecologically representative, well-connected, and effectively managed system of marine protected areas (MPAs) has positive ecological and environmental effects as well as social and economic benefits. Although progress in expanding the coverage of MPAs has been made, the application of management tools has not yet been implemented in most of these areas.2. In this work, distribution models were applied to nine benthic habitats on a Mediterranean seamount within an MPA for conservation purposes. Benthic ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 83 publications
3
23
0
Order By: Relevance
“…V. flagellum and Eunicella spp. on plateau regions, black corals on bench terraces), and was consistent with other surveys in the Mediterranean Sea (Bo et al, 2014b; Bo et al, 2015; Fourt et al, 2017; Giusti et al, 2017; de la Torriente et al, 2019). Furthermore, it is noteworthy how the presence of a heterogeneous sea floor, which in turn supports diversified deep‐sea assemblages, is frequently associated to volcanic sea floor (Ingrassia et al, 2019; de la Torriente et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…V. flagellum and Eunicella spp. on plateau regions, black corals on bench terraces), and was consistent with other surveys in the Mediterranean Sea (Bo et al, 2014b; Bo et al, 2015; Fourt et al, 2017; Giusti et al, 2017; de la Torriente et al, 2019). Furthermore, it is noteworthy how the presence of a heterogeneous sea floor, which in turn supports diversified deep‐sea assemblages, is frequently associated to volcanic sea floor (Ingrassia et al, 2019; de la Torriente et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Coralligenous on bedrock, the most abundant priority habitat observed in this study, hosted diverse benthic assemblages, over a bathymetric range comparable to that reported in other Italian seas (Ingrosso et al, 2018). At shallower depths, dense assemblages of suspension feeders formed a marine animal forest (sensu Rossi et al, 2017) (Bo et al, 2014b;Bo et al, 2015;Fourt et al, 2017;Giusti et al, 2017;de la Torriente et al, 2019).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We considered any model with an accuracy (explained deviance) of 0.4-0.6 as moderately sufficient (Maravelias et al, 2012) and models with an explained deviance of >0.6 to have relatively high explanatory power (Castella et al, 2001), whereas we considered CV values <0.3 as adequately precise (Peel et al, 2013). Previous studies have reported similar ranges in accuracy for other marine biota, including fish (0.14-0.55; Galaiduk et al, 2017), sessile invertebrates (0.04-0.68; Monk et al, 2018) and physical habitat structures (0.30-0.88; Torriente et al, 2019). That being said the accuracy and precision of most models in our study could be improved and would benefit from incorporating additional biotic variables, such as the extent of macroalgae canopy cover and occurrence of lobster, which have been linked to urchin density and barren formation (Johnson et al, 2005;Ling, 2008;Ling et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…The presence of multiple distinct morphologies of the deep seabed, such as, scars, channels, mud, rocks and sand, together with habitat-forming species (e.g., sponge, anemones and stylasterids corals) provide an environment that is home to numerous species, resulting in increases in diversity 16 , 60 . Besides, habitat-forming species are known to promote local complexity and heterogeneity of the seafloor at small (microhabitat) to large (macrohabitat) scales and to provide suitable refuge and nursery zone for smaller mobile benthic organisms 2 , 24 , 60 , 61 . Consistent with this pattern, it appears that OTU richness may be higher where habitat-forming species, such as sea pens ( Protoptilum and Scleroptilum ), anemones ( Hormathia sp.…”
Section: Discussionmentioning
confidence: 99%